2021
DOI: 10.1038/s41598-021-95387-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical cup placement affects the heating up of total joint hip replacements

Abstract: The long-term success of highly effective total hip arthroplasty (THA) is mainly restricted by aseptic loosening, which is widely associated with friction between the head and cup liner. However, knowledge of the in vivo joint friction and resulting temperature increase is limited. Employing a novel combination of in vivo and in silico technologies, we analyzed the hypothesis that the intraoperatively defined implant orientation defines the individual joint roofing, friction and its associated temperature incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In addition to these in vitro laboratory and in silico modelling studies, instrumented prostheses with various sensors were developed [672]. For example, such a technique allowed the measurement of in-vivo friction and temperature rise, showing the effect of the surgical cup placement on the heating up of total joint hip replacements [673]. Other in vivo methods were also applied, including using acoustic emission for the early detection of the failure modes in hip implants [674].…”
Section: Natural Synovial Joints and Artificial Joint Replacementsmentioning
confidence: 99%
“…In addition to these in vitro laboratory and in silico modelling studies, instrumented prostheses with various sensors were developed [672]. For example, such a technique allowed the measurement of in-vivo friction and temperature rise, showing the effect of the surgical cup placement on the heating up of total joint hip replacements [673]. Other in vivo methods were also applied, including using acoustic emission for the early detection of the failure modes in hip implants [674].…”
Section: Natural Synovial Joints and Artificial Joint Replacementsmentioning
confidence: 99%
“…The justification being that the plastic encapsulation of electronics should only be used for non-permanent implants [28]. To date no study has been reported from this prosthesis however, Bergmann et al [28] and Damn et al [36] state that a clinical study on temperature rise in hip implants was planned in 100 patients.…”
Section: D Force Measurements Acting On the Femoral Stemmentioning
confidence: 99%
“…An extended range of motion can avoid impingement in the hip joint prosthesis. Two general interactions that occur in a conventional dual-mobility hip joint prosthesis model are the acetabular cup with the liner and the liner with the femoral head, causing wear at two different locations 5,6 .Ultrahigh molecular weight polyethylene (UHMWPE) is a widely used material, especially as a bearing material for hip joint replacement surgery 7,8 . The type of UHMWPE used in the medical field has a molecular weight ranging from 3.5 to 6 million g/mol and has a degree of crystallinity ranging from 50 to 55% 9 .…”
mentioning
confidence: 99%
“…Ultrahigh molecular weight polyethylene (UHMWPE) is a widely used material, especially as a bearing material for hip joint replacement surgery 7,8 . The type of UHMWPE used in the medical field has a molecular weight ranging from 3.5 to 6 million g/mol and has a degree of crystallinity ranging from 50 to 55% 9 .…”
mentioning
confidence: 99%